Find the exact value of the inverse trig function expressions
Answer 1
Consider the expression $ \sin^{-1}\left( \frac{\sqrt{3}}{2} \right) $.
We know that $ \sin\left( \frac{\pi}{3} \right) = \frac{\sqrt{3}}{2} $.
Therefore, $ \sin^{-1}\left( \frac{\sqrt{3}}{2} \right) = \frac{\pi}{3} $.
Next, consider the expression $ \tan^{-1}(1) $.
We know that $ \tan\left( \frac{\pi}{4} \right) = 1 $.
Therefore, $ \tan^{-1}(1) = \frac{\pi}{4} $.
Finally, consider the expression $ \cos^{-1}\left( -\frac{1}{2} \right) $.
We know that $ \cos\left( \pi – \frac{\pi}{3} \right) = -\frac{1}{2} $.
Therefore, $ \cos^{-1}\left( -\frac{1}{2} \right) = \frac{2\pi}{3} $.
In summary:
$ \sin^{-1}\left( \frac{\sqrt{3}}{2} \right) = \frac{\pi}{3} $
$ \tan^{-1}(1) = \frac{\pi}{4} $
$ \cos^{-1}\left( -\frac{1}{2} \right) = \frac{2\pi}{3} $
Answer 2
Let
Answer 3
For $ sin^{-1}left( frac{sqrt{3}}{2}
ight) $,
it is $ frac{pi}{3} $.
For $ an^{-1}(1) $,
it is $ frac{pi}{4} $.
For $ cos^{-1}left( -frac{1}{2}
ight) $,
it is $ frac{2pi}{3} $.
Start Using PopAi Today